Resource Equivalency Analysis (REA): Implication environmental of groundwater in Kupang East Nusa Tenggara - Aplonia Bani; Suprihatin; SK Saptomo; RL Kaswanto (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
This article discusses the environmental assessment caused by the commercial use of groundwater by the community as landowners. In the future, this practice must receive direction and responsibility from the government as policymakers to prevent and repair environmental damage, especially habitat damage and species in strengthening the principle of